Pensar el cáncer de cuello de útero: Por un cambio de lentes (SigMe, 2023)
Cervical cancer (CC) continues to be a leading cause of mortality in women worldwide. Mortality rates express a positive trend for Argentina and the province of Santa Fe. Although the pathology is well known and there is primary, secondary and tertiary prevention, the effectiveness of these interventions seems to be limited. In this research paper, a genealogical critical analysis of the epistemological paradigms implied by different perspectives towards health-disease-care/prevention processes and their interventions on cervical cancer is carried out. It is postulated that the lens through which the disease is viewed cannot escape from the reductionist, atomized and deterministic foundation of health, despite its more sophisticated proposal: the social determinants of health. This model, in its pretension of being a comprehensive approach, as "risk epidemiology", restricts the view to the tip of the iceberg and becomes functional to the forms of civilization that promote inequalities. Critical epidemiology proposes, the concept of the social determination of health from complex thinking, making visible the relationship between social structure and health and the process of social reproduction in accordance with lifestyles. Thus, cervical cancer will be the product of a process of embodiment after the expression in the body of destructive or deteriorating conditions marked by gender, ethnic, and social class inequalities. From this analysis, the example of HPV self-sampling merges as a form of resistance and emancipatory counter-hegemonic bet against the pragmatic-functionalist model of health.
Keywords: epidemiology; knowledge; HPV infection; social vulnerability